PENGGUNAAN MEDIA GAMBAR SERI DALAM MODEL PEMBELAJARAN SECARA LANGSUNG UNTUK MENINGKATKAN BAHASA ANAK - Dina Khairiah; Nurul Amelia; Nadia Aisya; Silva Ardiyanti (IAIN Padangsidimpuan, 2020)
The main objective of this research is to explain that the serial image media has a sequence of images so that it can stimulate the child's mind to speak and produce a continuous story. This serial image media can increase children's interest in speaking so that children's language skills increase. The design of this research is classroom action research (PTK) using. The research instruments used included observations, tests, and field notes to measure teacher activity using observations, children's learning outcomes used test sheets while to find out the obstacles that arose during the implementation of learning. The analysis technique for observation and test data used descriptive and quantitative, while the analysis of field notes used descriptive and qualitative. The results of the study on the learning activities of the teacher's activity have increased from cycle I and cycle II. In the cycle, 1 teacher activity reached 78.3% and in cycle I teacher activity reached 93.3%. While the children's activity in cycle 1 reached 67.5% and cycle II children's activity reached 95%. Data on the results of children's tests in cycle 1 reached 66.7% and cycle I reached 86.7%. Based on the description above, it can be concluded that learning uses image media and direct learning models.Â